2011
DOI: 10.4314/ijhr.v3i3.70303
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Activity of Ethanolic Extract of the Stems of Anisochilus Carnosus against Carbon Tetrachloride-induced Hepatotoxicity in Rats

Abstract: and full-text of published articles. The journal is devoted to the promotion of health sciences and related disciplines (including medicine, pharmacy, nursing, biotechnology, cell and molecular biology, and related engineering fields). It seeks particularly (but not exclusively) to encourage multidisciplinary research and collaboration among scientists, the industry and the healthcare professionals. It will also provide an international forum for the communication and evaluation of data, methods and findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Several of these plant metabolites such as rotenoids (Boeravinone A-G), kaempferol, and quercetin have been proven for their role in hepatoprotective activity (Lami et al, 1990;Borrelli et al, 2005;Ferreres et al, 2005;Pereira et al, 2009;Bairwa et al, 2013). B. diffusa L. plant extract has been found to modulate CCl 4 induced liver injury in stimulated animals through the reduction of cytochrome (CYP) enzyme activities (Ramachandra et al, 2011;Venkatesh et al, 2012;Bairwa et al, 2013;Patel and Verma, 2014;Ekow Thomford et al, 2018;Juneja et al, 2020). P. niruri L. also known as 'bhumi amalaki' is composed of alkaloids, anthrocyanins, chlorogenic acids, flavonoids, lignans, phenolic acids, tannins, terpenoids, saponins, and substitutes that attribute to its bioactivity (Kaur et al, 2017;Jantan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several of these plant metabolites such as rotenoids (Boeravinone A-G), kaempferol, and quercetin have been proven for their role in hepatoprotective activity (Lami et al, 1990;Borrelli et al, 2005;Ferreres et al, 2005;Pereira et al, 2009;Bairwa et al, 2013). B. diffusa L. plant extract has been found to modulate CCl 4 induced liver injury in stimulated animals through the reduction of cytochrome (CYP) enzyme activities (Ramachandra et al, 2011;Venkatesh et al, 2012;Bairwa et al, 2013;Patel and Verma, 2014;Ekow Thomford et al, 2018;Juneja et al, 2020). P. niruri L. also known as 'bhumi amalaki' is composed of alkaloids, anthrocyanins, chlorogenic acids, flavonoids, lignans, phenolic acids, tannins, terpenoids, saponins, and substitutes that attribute to its bioactivity (Kaur et al, 2017;Jantan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The rise in serum levels of SGOT and SGPT has been attributed to damage in the structural integrity of the liver, since these enzymes are located in the cytoplasm and released into the blood after cell damage. 33,34 In our study, the infected animals showed SGOT and SGPT levels beyond the normal range. Our results are similar to the study performed by Kaur et al, 35 wherein L. donovani infected mice led to an increase in the liver function enzyme levels, indicating that the damage was due to severe hepatomegaly in leishmaniasis.…”
Section: Liver and Kidney Function Testsmentioning
confidence: 43%
“…A substantial number of herbal formulations have been affirmed to have medicinal properties to cure several life-threatening diseases (Sabir and Rocha, 2008;Akash et al, 2011;Akash et al, 2014a,b;Bhaskar and Balakrishnan, 2010;Huang et al, 2010;Venkatesh et al, 2010;Nayak et al, 2011;Rehman et al, 2012;Ibrahim et al, 2013;Hussain et al, 2014;Parveen et al, 2014). The plants that exhibit hepatoprotective effects, have the phytoconstituents such as phenyl compounds, coumarins, essential oils, monoterpenoids, diterpenoids, triterpenoids, steroids, alkaloids and other nitrogenous compounds (Sharma et al, 2011;Valan et al, 2010) that reveal hepatoprotective effects by preventing the liver from the damaging effects of drug-induced intoxication .…”
Section: Discussionmentioning
confidence: 99%